Psychopathology Factors That Affect the Relationship Between Body Size and Body Dissatisfaction and the Relationship Between Body Dissatisfaction and Eating Pathology - Rosewall, Juliet K.; Gleaves, David H.; Latner, Janet D. (Frontiers in Psychology, 2019)
Although high body mass index (BMI) alone does not invariably lead to body dissatisfaction (BD) and BD alone does not invariably lead to eating pathology (EP), research has suggested that there are clear relationships between each predictor and its respective criterion. We have a limited understanding of the factors that explain why some women at higher risk for BD (because of their BMI) do not report being dissatisfied with their bodies and why some women who are highly dissatisfied, do not engage in pathological eating behaviors. The present study examined such factors. A university sample of New Zealand women (N =166) completed the Personality Assessment Inventory (Morey, 1991) and questionnaires measuring BD and EP. The tendency to report lower BD than would be predicted by one’s BMI, and the tendency to report lower EP than would be expected based on one’s BD, were characterized by lower overall distress (i.e., lower levels of anxiety and depression) and greater mood stability compared to those who followed the predicted outcome. Greater understanding of the factors that protect high-risk women from BD and EP may contribute to prevention and intervention strategies.